PENERAPAN PEMBELAJARAN MODEL PROBLEM BASED LEARNING DALAM MENINGKATKAN KEMAMPUAN MEMECAHKAN MASALAH HAM DALAM MATA PELAJARAN PKn - Neldison, Neldison (Fakultas Ilmu Sosial Universitas Negeri Padang, 2014)
The objective of this study is to increase the ability of problem solving in human right issues through problem based learning model among students at SMA Negeri 4 Solok Selatan. This study was classroom action research and conducted in two cycles. The results of this study showed an increase in ability of the students in solving the problems of human rights. It means that the use of problem-based learning instructional model can build creative activity among students at SMA Negeri 4 Solok Selatan. Key Words: Problem solving ability, human rights, problem based learning model